The Adoption of Enterprise Architecture by Public Sector Organizations : Research in Brief - Ahmad N.A.; Drus S.M.; Kasim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Coercive pressures; Enterprise Architecture; Institutional theory; Normative pressures; Operational review; Organizational levels; Public sector organization; Technology-organization-environment frameworks; Decision making